Health Education with Leaflet Media on the Level of Knowledge of Mother's about Toddler Rearing Partners in Stunting Prevention - Achjar, Komang Ayu Henny; Marni , Ni Komang; Lestari, Agus Sri; Ribek, I Nyoman (LPPM Undiksha, 2023)
Stunting is a condition of toddlers who have a length or height that is less when compared to age. Stunting can have a bed impact on toddlers, namely short-term and long-term impacts that need to be watched out for early on. This study aims to analyze effect of health education with media leaflets on the level of knowledge of mothers about toddler parenting in stunting prevention. This type of research is pre-experimental by using simple random sampling technique. The population in this study was 708 people using 88 samples. Data was collected by using a questionnaire of knowledge. The results showed an increase in the knowledge of respondents who had good knowledge from 77 respondents (87.5%) to 85 respondents (96.6%), with sufficient knowledge to decrease from the initial 11 respondents (12.5%) to 3 respondents (3.4%), and there are no respondents who have less knowledge. The results of this study have been tested using the Wilcoxon test, the p-value = 0.000 < alpha (0.05), this means that Ha is accepted so that there is an effect of health education with media leaflets on the level of knowledge of mother's about toddler parenting in stunting prevention.